2022
DOI: 10.18280/ria.360601
|View full text |Cite
|
Sign up to set email alerts
|

Accurate Reader Identification for the Arabic Holy Quran Recitations Based on an Enhanced VQ Algorithm

Abstract: The Speaker identification process is not a new trend; however, for the Arabic Holy Quran recitation, there are still quite improvements that can make this process more accurate and reliable. This paper collected the input data from 14 native Arabic reciters, consisting of “Surah Al-Kawthar” speech signals from the Holy Quran. Moreover, this paper discusses the accuracy rates for 8 and 16 features. Indeed, a modified Vector Quantization (VQ) technique will be presented, in addition to realistically matching th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…Garcia-Sanchez et al [22] observed a high linear correlation between CTDI vol and SSDE. Similar results could be obtained using clustering algorithms [32] and numerical methods [33]. Sebelego et al [34] proposed a study aiming to determine the factors that impact SSDE for chest-abdomen-pelvis and abdomen-pelvis CT exams.…”
Section: Discussionsupporting
confidence: 55%
“…Garcia-Sanchez et al [22] observed a high linear correlation between CTDI vol and SSDE. Similar results could be obtained using clustering algorithms [32] and numerical methods [33]. Sebelego et al [34] proposed a study aiming to determine the factors that impact SSDE for chest-abdomen-pelvis and abdomen-pelvis CT exams.…”
Section: Discussionsupporting
confidence: 55%
“…Research on the Holy Quran improves speaker identification systems, recognizing Arabic and English speakers using 14 professional reciters' speech signals, with improved LBG-VQ algorithm matching codebook centroids with 96.43% accuracy [11]. The review highlights the effectiveness of deep learning in energy forecasting, highlighting the use of various neural networks, including simple RNN, LSTM, GRU, and bidirectional RNN [12]. The research introduces an efficient odometry method for autonomous path planning, enabling global optimal planning, mapping, and localization in static obstacles, improving computing speed and position accuracy [13].…”
Section: Opinion Miningmentioning
confidence: 99%
“…Every human being has different intentions and goals in memorizing the Qur'an (Mahmoudi, 2019;Wasfey, 2022). There are people who intend because they want to get a reward from Allah and there are also those who have other intentions (Ahmad, 2019;Alhourani, 2022;Al-Jarrah, 2022). The intention to memorize the Al-Qur'an must be straightened before someone wants to memorize the Al-Qur'an.…”
Section: Introductionmentioning
confidence: 99%